2022
DOI: 10.3390/ijms23042142
|View full text |Cite
|
Sign up to set email alerts
|

IQM-PC332, a Novel DREAM Ligand with Antinociceptive Effect on Peripheral Nerve Injury-Induced Pain

Abstract: Neuropathic pain is a form of chronic pain arising from damage of the neural cells that sense, transmit or process sensory information. Given its growing prevalence and common refractoriness to conventional analgesics, the development of new drugs with pain relief effects constitutes a prominent clinical need. In this respect, drugs that reduce activity of sensory neurons by modulating ion channels hold the promise to become effective analgesics. Here, we evaluated the mechanical antinociceptive effect of IQM-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 53 publications
(92 reference statements)
0
2
0
Order By: Relevance
“…Whether an increase in the dosage or a change in administration pattern of RP could render a significant effect on motor coordination, body weight loss, or lifespan in ALS mice remains to be investigated. Moreover, the potential benefits of the new DREAM binding molecules of the PC-series, like PC330 or PC260 [14,[88][89][90][91], in SOD1G93A mice remain to be investigated. Noteworthy, the SOD1G93A mouse model is a quite aggressive model of familial ALS, showing a very early onset and very fast disease progression [92].…”
Section: Discussionmentioning
confidence: 99%
“…Whether an increase in the dosage or a change in administration pattern of RP could render a significant effect on motor coordination, body weight loss, or lifespan in ALS mice remains to be investigated. Moreover, the potential benefits of the new DREAM binding molecules of the PC-series, like PC330 or PC260 [14,[88][89][90][91], in SOD1G93A mice remain to be investigated. Noteworthy, the SOD1G93A mouse model is a quite aggressive model of familial ALS, showing a very early onset and very fast disease progression [92].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a novel KChIP3 ligand, IQM-PC332, was reported to reduce mechanical hypersensitivity in rats subjected to chronic constriction injury of the sciatic nerve. Mechanistically, IQM-PC332 binds to KChIP3 and reduces ionic currents mediated by TRPV1 channels, K V 4.3 channels, low-voltage-activated T-type Ca 2+ channels, and high-voltage-activated Ca 2+ channels in DRG neurons [136]. This is a potential chemical tool and the elucidation of the structural basis of the analgesic effect of IQM-PC332 will be one of the possible steps towards a better understanding of how KChIP3 controls pain.…”
Section: Painmentioning
confidence: 99%
“…In addition, K V 4.2 channels play an important role in both synaptic plasticity and cognition, which in part contributes to the regulatory effect of KChIP3 on learning and memory [144]. channels, low-voltage-activated T-type Ca 2+ channels, and high-voltage-activated Ca 2+ channels in DRG neurons [136]. This is a potential chemical tool and the elucidation of the structural basis of the analgesic effect of IQM-PC332 will be one of the possible steps towards a better understanding of how KChIP3 controls pain.…”
Section: Memory Dysfunctionmentioning
confidence: 99%
“…It has been reported that IQM-PC332, a ligand of KChIP3, can reduce mechanical hypersensitivity in mice with chronic constriction injury of the sciatic nerve. Mechanistically, IQM-PC332 binds to KChIP3 and reduces ionic currents mediated by TRPV1 channels, KV4.3 channels, low voltage-activated T-type Ca 2+ channels and high voltage-activated Ca 2+ channels in DRG neurons [121].…”
Section: Painmentioning
confidence: 99%